KEBIJAKAN INDIA MENAHAN DUTA BESAR ITALIA UNTUK INDIA PADA INSIDEN ENRICA LEXIE TAHUN 2013 - Dinda Ulfah Damanik; Yuli Fachri (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2016)
Integration Course emerged as an integration course program which is the renewal of the license under the Migration Act related to the National Migration Integration as steps to improve the conditions of immigrants in Germany. But there are several obstacles in the Integration Course that immigrants who come from different corners of the world and immigrated in Germany will be the acculturation effect on social life in Germany, the lack of protection of all immigrants of all religions, and there is a shift in the demographic features native German speakers ,Qualitative research method is descriptive that will describe, record, analyze and interpret the condition or event associated with the problems posed and to develop the data obtained from various sources. The qualitative research to understand an issue or social phenomena are presented descriptively or with an explanation.The purpose of this paper is, in order to determine the condition of immigrants, knowing the background of the formation Integration Course, determine the effect or against immigrants in Germany. Because immigrants are people who want to get a life assured, adequate, safe, then Germany as a country that receives immigrants with a high amount, must pay attention to guarantee the lives of the immigrants.Keywords: Immigrant, Germany, Integration Course